La Restauration des sièges du Salon rouge de l’hôtel de la Chancellerie entre usages contemporains et patrimoine - Amandine Cambet; Thomas Deshayes; Carolina Hall; Antoine Meissonnier (In Situ)
In the Bourvallais hotel, headquarters of the French Ministry of Justice for more than 300 years, there are several pieces of furniture classified as “historic monuments”. Among them, there is a remarkable set of 33 mahogany seats with bronze, probably dating from the Bourbon Restoration, characterized by their protomes with lion heads and clawed feet. After years of preparation and waiting, these seats are now undergoing a complete restoration programme.At the end of this study, lacks still remain on the history of the furniture with lion heads from the Ministry of Justice: the conditions of order and arrival at the Bourvallais hotel are not certain, nor the identity of the author. But the information collected in the archives attests to the importance of this first-rate ensemble, from the end of the 1820s. It is not just one of several pieces of furniture, but the main ceremonial ensemble from the Chancellery hotel. After a period of relative oblivion under the French Third Republic, the furniture with lion heads finds its initial vocation of prestige representation in a new setting, the Empire living room, which takes over the function of the hotel's formal living room.The fact that the furniture is still in use must be taken into account in the choice of the upholstery: the choice of a crimson silk embroidered with golden patterns was a compromise, but established on historically documented models. Likewise, the padding was carried out according to the old methods. As for the restoration of the woods, it was done according to heritage restoration standards, aiming at the maximum conservation of old materials.